Mendongkrak Nilai Jual Produk UMKM Desa Keseirejo Melalui Sertifikasi Halal dan Pemasaran Digital - Wulan Suryaningsih; Ana Ristiana; Naily Himmatul Ulya; Ika Rinanti; Hana Fahmilia; Sigit Yudhatama Prawira; Karimatul Khasanah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
One of the work programs of class 56 KKN students group 22 UIN K.H. Abdurrahman Wahid Pekalongan is increasing the selling value of MSME products in Keseirejo Village through halal certification and digital marketing. The targets for this activity are MSMEs who produce processed food and beverage products. This research includes objectives that contribute to the development of MSMEs so they are able to compete in an increasingly competitive market. The method used in this research is a survey to collect data from a number of MSMEs on a wider scale and direct dissemination of explanations. Observations in this research were carried out directly by visiting and observing the operational conditions of MSMEs. The results of the research show that halal certification and labeling is a form of reform in the food and public consumption sector. Halal certification and digital marketing can improve the people's economy.